STRATEGI KOMUNIKASI PEMASARAN PRODAK ERIGO TERHADAP INFLUENCE JKT48 - Shinta Zahra Maharani; Alya Putri Az-zahra (Cahaya Ilmu Bangsa, 2024)
This research examines the marketing communication strategy for the Erigo product and the influence of JKT48 by analyzing how the Erigo brand can leverage influencers to increase buyer interest, influence purchasing decisions for Erigo products, and enhance brand awareness. It was found that the marketing communication strategy for the Erigo product can significantly increase purchases, enhance buyer interaction with the brand, and also influence, in line with expectations. From the results of this research, it shows that companies can view the use of influence in a brand as a tool for productivity and progress for the brand and also the products being sold.